Presenting Successful Wildlife Education Programs– Engaging Your Audience - Lord, Jeannie (Wildlife Rehabilitation Bulletin, 2005)
A wildlife educator walks into a room and sees the audience waiting eagerly. Walking into that classroom or auditorium, you, the educator, find a ‘captive’ audience filled with interest in who you are and what you do. The term ‘wildlife rehabilitator’ connotes an association with mammals, birds, or reptiles, and to many audiences that is intriguing. The fact that you may be accompanied by either live educational mammals or birds, mounted specimens, or an assortment of exciting wildlife artifacts creates an additional degree of anticipation and arouses curiosity in all age groups. Your skills and experiences can create the perfect atmosphere for conveying important facts and concepts regarding wildlife rehabilitation, in addition to your personalized message to benefit wildlife. You should feel comfortable and confident if you have done your advance planning and preparation.